Factors associated with utilization of Iron with Folic Acid (IFA) supplement among pregnant women attending antenatal care at government health facilities and family guidance clinic in Hawassa City Administration, Hawassa, Ethiopia - Merse, Fekadu; Kelbiso, Lolemo; Fanta, Amanuel (Clinical Journal of Obstetrics and Gynecology, 2022)
Background: Iron deficiency anemia is common during pregnancy since the overall iron requirement is greater than non-pregnant women and is associated with adverse outcomes. Iron deficiency (ID) is a state of insufficient iron to maintain normal physiological functions of tissues and leads to anemia. Objectives: To assess factors associated with the utilization of Iron with Folic acid supplement Among Pregnant Women Attending Antenatal care at Government Health Facilities and Family Guidance Clinic in Hawassa City, South Ethiopia. Methods: Institutional-based cross-sectional study design was conducted among 412 health providers who are working at public health institutes in Hawassa city from March to April 2015. Pretested Self-administered questionnaires were used to collect the data. The data was entered into Epi-data and analysed by SPSS version 26.0. Bivariate and multivariate regression analysis was used to see the significant association between the outcome and independent variables. Odds ratios and 95% CI will be computed to measure the strength of the association, p - value of ˂ 0.05 will be considered a statistically significant. Results: A total of 412 pregnant women who came to attend ANC at least for the second time were interviewed in seven health facilities. Our study showed that 333 (81%, 95% CI: 77.2 - 84.8) pregnant women reported taking IFA supplements and high compliance was 37.7% (95% CI: 32.5 - 42.9). In multivariable analysis, side effects and low acceptance of the supplement were significantly associated with compliance to IFA supplementation (p < 0.05). Conclusion: There is a relatively better level of compliance towards IFA supplementation compared to other national data. Pregnant women should be counseled regarding how to manage the side effects of IFA supplements during ANC. Further research has to be done on the acceptability of the supplements.